Robert B. Parker's broken trust : a Spenser novel [compact disc, unabridged] - Parker, Robert B., 1932-2010; Lupica, Mike (Parker, Robert B., 1932-2010 Spenser novel, 2023)
The beautiful wife of one of the world's richest men comes to Spenser hoping that he can find out what skeletons lurk in her husband's closet. Though he is a generous philanthropist and loving family man, she is concerned, he has recently become secretive, bordering on paranoid, and she wants Spenser to find out why. As Spenser digs into the billionaire's past, he realizes that the man may have done terrible things on his rise to the top, but he also may have had good reason to. What Spenser discovers will cause him to question his own views on morality, and place him in grave danger.